Lower Cretaceous ammonites from the Neuquén Basin, Argentina: the Hauterivian neocomitid genusHoplitocrioceras (Giovine, 1950) - Aguirre-Urreta, Maria Beatriz (2001)
Hoplitocrioceras is a poorly-known ammonite genus of late Early Hauterivian age that may be endemic to the Neuquén Basin Argentina where it occurs at a clearly defined horizon in the Agrio Formation. It is an unusual genus with uncoiling (crioceratitid) whorls that remain linked by a thick dorsal shell that drapes over the tips of sharp upwardly-pointing ventro-lateral spines. It has been interpreted as either a necomitis or a crioceratitid but is here regarded as one of the last members of the Family Neocomitidae. One new species is proposed: H. giovinei.